Is Bodyweight-Based Dosing Truly Better Than Flat Dosing for Panitumumab? [Response to Letter] - Liao MZ; Kast J; Berkhout M; Prenen H; Dutta S; Upreti VV (Dove Medical Press, 2020)
Michael Z Liao,1 Johannes Kast,1 Marloes Berkhout,2 Hans Prenen,3 Sandeep Dutta,4 Vijay V Upreti1 1Clinical Pharmacology, Modeling & Simulation, Amgen Inc., South San Francisco, CA, USA; 2Amgen B.V., Breda, the Netherlands; 3Antwerp University Hospital, Edegem, Belgium; 4Clinical Pharmacology, Modeling & Simulation, Amgen Inc., Thousand Oaks, CA, USACorrespondence: Vijay V UpretiClinical Pharmacology, Modeling & Simulation, Amgen, 1120 Veterans Boulevard, South San Francisco, CA 94080, USAEmail vupreti@amgen.com Thank you for the opportunity to respond to the letter by Dr. Hendrikx and colleagues. We wish to thank Dr. Hendrikx and colleagues for their interest in our recent publication by Liao et al1 and their comments about the optimal dosing regimen for panitumumab. The body weight-based dosing, 6 mg/kg once every two-week (Q2W) regimen, for panitumumab as an optimal dosing regimen is fully supported by clinical study data and pharmacokinetic modeling and simulations.2   View the original paper by Liao and colleagues   This is in response to the Letter to the Editor